(3fJGFL GdCacGQ aj TQM GdEXgGQ ddHQcdjs - (3GdCWg dj (B( (3CVdj (B) (3GdJQcj, BWg dj, eUWai Hf MeRI Hf EHQGgje, J HYO (B1085(3g`s ((3Ydj GdhUaj Hf CMeOs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdCdaGX bhGdH GdeYGfj haVdgG Ydi SGFQ GdCUhGJ CeG HYO ajbhd GdYHO GdabjQ eUWai Hf MeRI Ef cJGH EXgGQ GdCSQGQ ddaGVd ehdGfG eMeO GdeYQha HGdHQchj eTJedG Ydi eSGFd ObjbI hJMbjbGJ YejbI SCdfj HYV GdENhGf Cf CcJH dge TQMG jMd YbO CdaGXg SejJg fJGFL GdCacGQs
(3BNQgG (B:s
(3dhLhO GdaUd HGdYWa hdPG de jJYQV dg dCf cdGeg aj LGFR GdHfGA hEfeG de jJYQV dMce SGFQ GdJhGHY CjVG dCfg dG fU Yfge ajgG ZjQ Cfg fbd Yf GdCfOdSj Cf eG YOGgeG cJhGHY GdefGOis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 232s
(3eYLe GdeDdajf(B: 3 / 863s
(3EjVGM Gdecfhf(B: 2 / 620s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs